The Synergy/Integration between Intelligence & Capital in the light of the Qura’an & Sunnah from Sustainable Developmental Perspective - Salem, Mamoon Yousef (Journal of Humanities & Social Sciences, 2021)
This research aims to clarify the synergy (bond/integration) between the Capital and the Intelligence in light of the Qura’an and Sunnah from sutainable developmental perspective, in the other way its attentively enlightens the meanings of versus of Quran and Sunnah in sustainable way; The research methodology was based ubon Tracking the Holy Quraan & Sunnah to reveal/explain the link/connection between capital and Intelligance mentioned in it, the researcher reaches that there is strong integration between the types (Capital& Intelligence) in examples (Role Models/leaders) from Quran and Sunnah in order to achieve peace, prosperity and sustainability to the community, and it reveals that Quran and true sunnah has a biggest influence in supporting this Coalition by setting such these examples and with the guidance of Allah and its prophet Mohammed (ppuh) reactions (sayings, doing and approval), taken in consideration not to twist the versus of Quran or hadith to comply/ match with the subject of the research; and the results of this study that there is a strong sustainable relationship between all types of capital and intelligence supported by Quran and reinforced by Sunnah, in fact there is a solid bond between intelligence and capital shown in Quran and Sunnah for the sake of humanity, also Quran and Sunnah encourages transparency and positivity in all ways of life (relationships, thoughts, communications,..) in sustainable moral frame to achieve Eternity in this life and at the judgment day; And the recommendations is that It’s Important for Islamic Institutes to support like these researches effectively to enhance the sustainable human development in the society, further more It’s crucial to implement the intelligence types by Institutes in Islamic perspective in all ways of life (educational, cultural, social,..) to build a generation proud of his Islam and ready to work for it.
Keywords: integration; capital; intelligence; the Holy Quran and the Sunnah